Pressure Hull Analysis under Shock Loading - Ya-Jung Lee; Chia-Hao Hsu; Chien-Hua Huang (Shock and Vibration)
The hull of high performance submarines must resist underwater shock loading due to exploding torpedoes or depth bombs. An underwater shock involving an initial shock wave and successive bubble pulsating waves is so complex that a theoretical technique for deriving shock pressure distribution is required for improving simulation efficiency. Complete shock loading is obtained theoretically in this work, and responses of a submarine pressure hull are calculated using ABAQUS USA (Underwater Shock Analysis) codes. In the long run, this deflection and stress data will assist in examining the structural arrangement of the submarine pressure hull.